2022
DOI: 10.3889/oamjms.2022.8582
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Avocado (Persea Americana Mill.) Peel Extract on the Diabetic Male White Rats: Preclinical Study

Abstract: Background: Type 2 Diabetes Mellitus (DMT2) is one of the most common non-communicable diseases (NCDs) worldwide. T2DM is also the leading cause of death in most developed and developing countries. Objective: This study aimed to analyze the effect of avocado (Persea americana Mill.) skin extract on blood glucose levels in white male rats with diabetes (preclinical test). Method: Experimental research in vivo with True Experimental-PreTest and Post Test Only Control Group Design. The samples were 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…The results showed that the dose of avocado leaf extract affected the level of kidney damage, where the higher the dose of the extract given, the lower the level of kidney damage that occurred. The 200 mg/kg bw dose of avocado leaf extract showed the most positive results with no detectable signs of kidney damage (Rahman et al, 2022).…”
Section: Avocado Fruit Peel Extract and Antidiabeticmentioning
confidence: 94%
See 3 more Smart Citations
“…The results showed that the dose of avocado leaf extract affected the level of kidney damage, where the higher the dose of the extract given, the lower the level of kidney damage that occurred. The 200 mg/kg bw dose of avocado leaf extract showed the most positive results with no detectable signs of kidney damage (Rahman et al, 2022).…”
Section: Avocado Fruit Peel Extract and Antidiabeticmentioning
confidence: 94%
“…The research results of Rahman et al (2022) regarding the effect of avocado peel extract on male white rats with diabetes showed differences in response to fasting blood glucose levels between the treatment groups (Rahman et al, 2022). The results showed that avocado peel extract at certain doses did not significantly reduce fasting blood glucose levels in several treatment groups.…”
Section: Avocado Fruit Peel Extract and Antidiabeticmentioning
confidence: 97%
See 2 more Smart Citations
“…Hasil penelitian dari (Rahman et al, 2022)juga menemukan bahwa konsentrasi 200 mg/kg BB buah alpukat ekstrak kulit secara signifikan mengurangi glukosa darah puasa kadarnya sebesar 133,33 mg/dL setelah induksi STZ dibandingkan kepada kelompok lain. Konsentrasi yang terlalu rendah dan tinggi ekstrak kulit alpukat tidak menunjukkan pengaruh yang signifikan dan perubahan positif dalam meningkatkan glukosa darah puasa tingkat pada tikus (Rahman et al, 2022).…”
Section: Pembahasanunclassified